Children and Adolescents with Complex Regional Pain Syndrome: More Psychologically Distressed than Other Children in Pain? - Deirdre E Logan; Sara E Williams; Veronica P Carullo; Robyn Lewis Claar; Stephen Bruehl; Charles B Berde (Pain Research and Management)
BACKGROUND: Historically, in both adult and pediatric populations, a lack of knowledge regarding complex regional pain syndrome (CRPS) and absence of clear diagnostic criteria have contributed to the view that this is a primarily psychiatric condition.